The Stoic theory of value and psychopathology. Does the ideal of apathy have a neurotic character? - Banicki, Konrad (Diametros, 2006)
Psychological questions within philosophical ethics, although very often deeply distrusted, are justified if we presume the ultimate unity of the ethical and psychosocial subject. Such questions are especially well-grounded when we deal with a philosophy that is as practical as Stoicism. Because of both their contents and origins, the theories of values and emotions proposed by this ancient school may attract the suspicious attention of psychologists. For there are good reasons to suggest that the ideas in question were neurotic – that they arose from and caused neurosis. This hypothesis can be verified within the framework of Paul Tillich’s multidisciplinary conception of neurosis. After a somewhat more detailed analysis, it turns out that the Stoic conception is in principle neither the result nor the cause of neurotic disturbances. Furthermore, it seems that it is quite the contrary – it causes people to flourish psychologically and existentially. It must nevertheless be emphasized that Stoic philosophy, if misunderstood or led astray (Ariston), still might (have) become neurotic in character.